A Systematic Review of Parental Occupational Pesticide Exposure and Geographical Proximity to Agricultural Fields in Association with Neural Tube Defects - Karoline Felisbino; Shayane da Silva Milhorini; Nathalia Kirsten; Mariane Yoshie Sato; Davi Paula da Silva; Juliana Danna Kulik; Izonete Cristina Guiloski (Toxics)
Neural tube defects (NTDs) are the second most common congenital anomaly and have been widely associated with exposure to pesticides. This systematic review which analyzes the association between parental exposure to pesticides and NTDs was conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. The search strategy was designed considering the population, exposure, controls, outcomes, and study design (PECOS). The inclusion criteria were epidemiological studies involving pesticides exposure during embryonic development, written in English, Portuguese, or Spanish, and performed in 12 databases. Based on the eligibility criteria, 16 articles were selected for analysis. The most frequently assessed NTDs were anencephaly and spina bifida, with 14 studies investigating each of these conditions. The assessment of pesticide exposure was based on parental occupation and residential proximity to agricultural fields. Studies differed regarding the pesticides assessed, exposure windows, and parents exposed. Regarding the outcomes, it was observed that geographic proximity to agricultural fields and a greater association with family members exposed to pesticides were found in mothers and neonates with NTDs. In relation to occupational exposure, some articles found an association with NTDs, while others did not. Therefore, an analysis of the available evidence suggests that pesticides are a risk factor in the development of NTDs.